2020
DOI: 10.1108/ijmpb-01-2020-0033
|View full text |Cite
|
Sign up to set email alerts
|

Investigating collaboration in project management research: using action research as a meta-methodology

Abstract: PurposeThe purpose of this article is to investigate collaboration in project management research. Although the literature shows an increase in collaboration between scientists and social scientists for various reasons, it is unclear how and why such collaboration takes place in project management research. The literature does show that co-authorship of articles published in project management journals is on the rise due to increased collaboration between researchers in developed countries and emerging economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 46 publications
(63 reference statements)
0
13
0
Order By: Relevance
“…Operations management is the field of management in which AR is mostly used (Erro-Garcés & Alfaro-Tanco, 2020). But as there are studies that highlight the relevance of AR in other fields of management, such as marketing (Kates & Robertson, 2004), human resources (Githens, 2015), information systems (Baskerville & Wood-Harper, 1996) or project management (Sankaran et al, 2021), some of the findings of this study can hopefully be valuable for other fields of management. More specifically, the evaluation framework developed represents a tool that may help to assess the dual contribution of any research study based on AR and not only in the field of OM.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Operations management is the field of management in which AR is mostly used (Erro-Garcés & Alfaro-Tanco, 2020). But as there are studies that highlight the relevance of AR in other fields of management, such as marketing (Kates & Robertson, 2004), human resources (Githens, 2015), information systems (Baskerville & Wood-Harper, 1996) or project management (Sankaran et al, 2021), some of the findings of this study can hopefully be valuable for other fields of management. More specifically, the evaluation framework developed represents a tool that may help to assess the dual contribution of any research study based on AR and not only in the field of OM.…”
Section: Discussionmentioning
confidence: 95%
“…On the one hand, Erro-Garcés and Alfaro-Tanco (2020, p. 8) concluded that "AR is a multidisciplinary approach that involves the use of various qualitative and quantitative methodologies/ instruments and, consequently, enables the implementation of other quantitative and qualitative methodologies." On the other hand, Sankaran et al (2021) used action research as a metamethodology through the mix of case studies and surveys in order to investigate collaboration in project management research. Meredith et al (1989) defined AR as an ongoing cycle of research stages.…”
Section: Rigor As the Key Requirement To Enrich Research Contribution...mentioning
confidence: 99%
“…Like other research in the field that also draws on participant experiences, in reporting our results, we take the view that qualitative research, especially in-depth semi-structured interviews, needs to maintain participant voice (see Lindebaum and Fielden, 2011; McGrath and Whitty, 2020; Sankaran et al. , 2021; Pugh, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Scientists have found that doctoral students are not sufficiently aware of the proper use of project management methodologies, as a result of which there is a need to update the organizational framework. Scientists from Australia, Norway and Canada, namely S. Sankaran, R. Muller and N. Drouin, focused on the analysis of collaboration in project management research [3]. In particular, the authors draw attention to international cooperation between developed countries and developing countries, in the context of which the issue of research management is raised.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists also conducted an empirical study that provided for determining the prerequisites for international scientific and project cooperation, among which the reputation of leading researchers, the prestige of institutions, etc. were identified [3]. Especially important for scientific intelligence are the achievements of K. Piwowar-Sulej [4].…”
Section: Introductionmentioning
confidence: 99%